2013
DOI: 10.4021/gr522w
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Recurrent Esophageal Diverticulitis - A Rare Entity

Abstract: In this report, we seek to shed light on a 44-year-old Caucasian male with a known history of an esophageal diverticulum, who was transferred to our facility after an upper endoscopy at an outside hospital suggested a purulent discharge emanating from the mouth of a mid-esophageal diverticulum. A barium swallow done at the outside institution had reportedly demonstrated an 8 cm long barium collection parallel to and anterolateral to the mid-and distal esophagus which terminated several centimeters proximal to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…8,[15][16][17] Routine surgery for all epiphrenic diverticula regardless of symptoms is no longer in favor but was largely based on previous studies that demonstrated increased risk for aspiration pneumonia, perforation, diverticulitis, and malignant transformation. 9,[17][18][19] Symptoms of regurgitation and aspiration may correlate with larger diverticula, which can serve as a reservoir for food debris; however, most series have shown poor correlation between symptoms and diverticulum size. Symptoms can more commonly be attributed to accompanying…”
Section: Discussionmentioning
confidence: 99%
“…8,[15][16][17] Routine surgery for all epiphrenic diverticula regardless of symptoms is no longer in favor but was largely based on previous studies that demonstrated increased risk for aspiration pneumonia, perforation, diverticulitis, and malignant transformation. 9,[17][18][19] Symptoms of regurgitation and aspiration may correlate with larger diverticula, which can serve as a reservoir for food debris; however, most series have shown poor correlation between symptoms and diverticulum size. Symptoms can more commonly be attributed to accompanying…”
Section: Discussionmentioning
confidence: 99%